2020
DOI: 10.3389/fpsyt.2020.00217
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in Severity of Depressive Symptoms, Heart Rate Variability, and Neurocognitive Profiles of Depressed Young Adults: Exploring Characteristics for Mild Depression

Abstract: present results suggest that recognizing the early signs of MDS that account for sexspecific differences in both subjective and objective measures may improve the diagnosis and monitoring of young adults with MDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
8
0
1
Order By: Relevance
“…26 ( 15 – 20 , 22 37 , 42 , 44 , 45 , 47 , 55 ) studies reported the outcome indicator SDNN. 28 ( 15 – 26 , 28 , 29 , 31 , 33 – 35 , 38 , 40 42 , 44 , 45 , 47 , 49 , 50 , 52 , 55 ) studies reported the outcome indicator RMSSD. 13 ( 14 , 15 , 22 , 25 – 27 , 29 , 31 , 33 – 35 , 42 , 48 , 50 ) studies reported the outcome indicator PNN50.…”
Section: Resultsmentioning
confidence: 99%
“…26 ( 15 – 20 , 22 37 , 42 , 44 , 45 , 47 , 55 ) studies reported the outcome indicator SDNN. 28 ( 15 – 26 , 28 , 29 , 31 , 33 – 35 , 38 , 40 42 , 44 , 45 , 47 , 49 , 50 , 52 , 55 ) studies reported the outcome indicator RMSSD. 13 ( 14 , 15 , 22 , 25 – 27 , 29 , 31 , 33 – 35 , 42 , 48 , 50 ) studies reported the outcome indicator PNN50.…”
Section: Resultsmentioning
confidence: 99%
“…Diagnoses of major depressive disorder (MDD) or mild depressive symptoms (MDS) were made by licensed psychiatrists based on semi-structured MINI-International Neuropsychiatric Interviews. The classification criteria of the MDD and MDS participants have been reported as in previously published manuscripts ( 24 , 25 ). The MDD and MDS participants met at least one of the following criteria: Patient Health Questionnaire-9 ≥ 10 points; General Anxiety Disease-7 ≥ 10 points; State-Trait Anxiety Inventory-State ≥ 61 points (for males) or ≥65 points (for females); a history of at least 1 suicidal thought/attempt/plan within the past 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…This is our topic here. Although young adulthood is the peak period of new-onset major depression ( 2 ), young adults rarely seek treatment because most are unaware of their symptoms ( 24 ). Young adults are thus the optimal population for an intensive longitudinal study of the association between daily sleep variability and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of various treatment methods for depression, the treatment effects remain poor due to the lack of medical resources and difficulties in early detection of depression ( 11 ). As a result, a risk prediction model for depression is essential to facilitate early detection of this disease.…”
Section: Introductionmentioning
confidence: 99%